Analisis Penerimaan Aplikasi Pembelajaran Logika dan Desain Pemrograman dengan Menggunakan Technology Acceptance Model 2 (TAM 2) Pada Institut Bisnis dan Informatika Stikom Surabaya - Khurrosidin, Mifta; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Based on data obtained from the Development and Application of Information Technology (PPTI) Institute Business and Informatics Stikom Surabaya about 20%-30% students who have followed this course got score under B which means that the level of understanding of students to this course still lacking therefore made Application Learning Logic and Design Programming useful to help increase graduation in the course logic and design programming but after the application is implemented has never performed an evaluation of the acceptance application toward Usage Behavior. In analyzing acceptance Application Learning Logic and Design Programming is using method from Venkatesh dan Davis is Technology Acceptance Model 2 (TAM 2) to design a model. Based on the results of the deployment of 126 questionnaires to students S1 Information System that follows the course Logic and Design Programming and analyze using the method SEM, obtained results that Application Learning Logic and Design Programming can be received by students from Perceive Ease of Use factor which encourages interest student to use Application Learning Logic and Design Programming